(untitled) (Journal of actual problems of jurisprudence, 2018)
The article considers the principles of decriminalization as one of the means of criminal policy realization. The author suggests working out the criteria of referring crimes to the other offences and acts. In particular, in Special part of Criminal code it is necessary to point out the structures where the administrative measures could be applied. Moreover in the General part of the Criminal code it is also necessary to give the list of insignificant socially dangerous acts. Keywords: Criminal law, criminal policy, development of criminal policy, criminalization, decriminalization, crime, administrative offence, act/crime, realization of criminal policy, efficiency of criminal policy.